1990
DOI: 10.1111/j.1751-1097.1990.tb04193.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo TUMOR OXYGEN TENSION MEASUREMENTS FOR THE EVALUATION OF THE EFFICIENCY OF PHOTODYNAMIC THERAPY

Abstract: Among the sequence of events which occur during photodynamic therapy (PDT) are depletion of oxygen and disruption of tumor blood flow. In order to more clearly understand these phenomena we have utilized transcutaneous oxygen electrodes to monitor tissue oxygen disappearance. These results provide, for the first time, non-invasive real-time information regarding the influence of light dose on tissue oxygenation during irradiation. Measurements were conducted on transplanted VX-2 skin carcinomas grown in the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
93
1
9

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(112 citation statements)
references
References 18 publications
9
93
1
9
Order By: Relevance
“…This study confirms the concept of photochemical oxygen depletion during PDT, which was put forward by Tromberg et al (1990) and Foster et al (1991), and provides direct experimental evidence of PDT-induced oxygenation changes in a preclinical tumour system.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This study confirms the concept of photochemical oxygen depletion during PDT, which was put forward by Tromberg et al (1990) and Foster et al (1991), and provides direct experimental evidence of PDT-induced oxygenation changes in a preclinical tumour system.…”
Section: Discussionsupporting
confidence: 87%
“…This observation is consistent with the concept of photochemical oxygen depletion and observations by Tromberg et al (1990), and does not agree with the finding by Fingar et al (1992b) of PDTinduced vascular constriction lasting for -1 h after treatment. (3) The observed recovery of tumour pO2 at low fluence rate with low-treatment fluence may be due to a decrease in metabolic oxygen consumption as a result of direct cell effects during PDT (Gibson et al, 1990), i.e.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…16 Tromberg et al 17 observed that during PDT using high fluence rate, oxygen depletion occurs with temperature increase. Following their conclusions, if the hyperthermia effect is high enough to contribute to the therapeutic process, the induction of the synergistic effect may have taken place, enhancing tissue damage during PDT.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also concluded lower fluence rate treatments can preserve the status of oxygen for a more effective PDT [6,9,17,18], and it has been recognized that light fluence rates play a major role in the tumor oxygenation status during PDT exposure. Our work explains the mechanism of oxygen preservation under low fluence illumination in PDT to some extent.…”
Section: Discussionmentioning
confidence: 99%